Sports financing in Croatia - Borbély, Tamás (Applied Studies in Agribusiness and Commerce, 2015)
Sport is a complex social activity that encompasses various areas. Some of these activities come within the category of public needs, which implies that sport is an activity of wider social interest and requires public intervention in its financing. These needs are determined by law and are an integral part of state and local budgets. It is also indisputable that the sport is an activity of exceptional significance for the society and it is equally clear that the investment into sport in Croatia is not proportional to that significance and top scores, which are achieved by the Croatian athletes. Sport can be in a partner relationship with the economy and the promoter of social changes and habits, but in order to become and remain that, general public has to be truthfully interested into sports.